2014
DOI: 10.1007/s10549-014-3040-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of metastasis-associated genes identifies miR-17-5p as a metastatic suppressor of basal-like breast cancer

Abstract: The purpose of this study is to identify metastasis- associated genes/signaling pathways in basal-like breast tumors. Kaplan–Meier analysis of two public meta-datasets and functional classification was used to identify genes/signaling pathways significantly associated with distant metastasis free survival. Integrated analysis of expression correlation and interaction between mRNAs and miRNAs was used to identify miRNAs that potentially regulate the expression of metastasis-associated genes. The novel metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 55 publications
1
35
0
1
Order By: Relevance
“…TAOK1 had a relatively low p-value by Limma (E-04) but the 3 other associations are specific to our test and correspond to low values of r . TAOK1 was previously listed as a metastasis-associated genes in basal-like breast tumors [18] (through expression). RALB , also known as RAS Like Proto-Oncogene B, which is known for its role in invasion and metastasis across cancers and specifically for breast cancer [76].…”
Section: Resultsmentioning
confidence: 99%
“…TAOK1 had a relatively low p-value by Limma (E-04) but the 3 other associations are specific to our test and correspond to low values of r . TAOK1 was previously listed as a metastasis-associated genes in basal-like breast tumors [18] (through expression). RALB , also known as RAS Like Proto-Oncogene B, which is known for its role in invasion and metastasis across cancers and specifically for breast cancer [76].…”
Section: Resultsmentioning
confidence: 99%
“…We identified eight miRNAs significantly associated with BMI with the strongest positive associations as miR_22_3p(r=0.26, p=0.004) and miR_122_5p(r=0.25, p =0.005), both of which are implicated in BC metabolism 6365 . miRNAs with the strongest negative BMI association was miR_191_5p(r=−0.22, p =0.016) and miR_17_5p(r=−0.22, p =0.017), which are implicated in BC progression 66, 67 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have indicated that the function of miR-17-5p appears to be conflicting in different cancer cell types. Fan et al (27) reported that miR-17-5p serves a role in suppressing epithelial mesenchymal transition and metastasis in breast cancer cells. However, another study demonstrated that the downregulation of miR-17-5p contributes to the resistance of lung cancer cells to paclitaxel (28).…”
Section: Discussionmentioning
confidence: 99%